2000
DOI: 10.1128/jvi.74.11.5300-5309.2000
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Major Histocompatibility Complex Class I Molecules by Kaposi's Sarcoma-Associated Herpesvirus K3 and K5 Proteins

Abstract: The T-cell-mediated immune response plays a central role in the defense against intracellular pathogens. To avoid this immune response, viruses have evolved elaborate mechanisms that target and modulate many different aspects of the host's immune system. A target common to many of these viruses is the major histocompatibility complex (MHC) class I molecules. Kaposi's sarcoma-associated herpesvirus (KSHV) encodes K3 and K5 zinc finger membrane proteins which remove MHC class I molecules from the cell surface. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
323
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(335 citation statements)
references
References 40 publications
11
323
0
1
Order By: Relevance
“…98 In addition, the KSHVencoded K3 and K5 proteins also differentially affect MHC class I antigen expression: the K3 protein significantly downregulates HLA-A, -B, -C and -E antigens, whereas the K5 protein selectively suppresses the expression of HLA-A and -B, but not that of HLA-E antigens. 99 This difference is attributable to altered amino acid sequences in the transmembrane region of the respective HLA class I antigens. 71 Recently, it has been shown that the HPV E5 protein specifically downregulates HLA-A and -B gene transcription.…”
Section: Hla Class I Antigen Downregulationmentioning
confidence: 99%
“…98 In addition, the KSHVencoded K3 and K5 proteins also differentially affect MHC class I antigen expression: the K3 protein significantly downregulates HLA-A, -B, -C and -E antigens, whereas the K5 protein selectively suppresses the expression of HLA-A and -B, but not that of HLA-E antigens. 99 This difference is attributable to altered amino acid sequences in the transmembrane region of the respective HLA class I antigens. 71 Recently, it has been shown that the HPV E5 protein specifically downregulates HLA-A and -B gene transcription.…”
Section: Hla Class I Antigen Downregulationmentioning
confidence: 99%
“…MIR family proteins bind to the membrane through their hydrophobic domains located at the center and possess two intracellular regions. The initially discovered MIR family proteins are viral E3s: MIR1 and MIR2 of Kaposi's sarcoma-associated herpesvirus (KSHV), mK3 of murine ␥-herpesvirus 68, and m153R of myxomavirus (3,(5)(6)(7)(8)(9). Each molecule targets a different set of Ag presentation-related molecules: CD1d and MHC class I (MHC I) for MIR1; B7-2, ICAM-1, CD1d, and MHC I for MIR2; MHC I for mK3; MHC I, CD4, and Fas for m153R (3, 5, 9 -12).…”
Section: Inhibition Of Mhc Class II Expression and Immune Responses Bmentioning
confidence: 99%
“…They function as membrane-bound ubiquitin ligases, leading to ubiquitination of their target proteins on lysine residues in their cytosolic tails (32). The result of this ubiquitination is the enhancement of the endocytosis of the target chain and its delivery (via the multivesicular body) to the lysosome, where it is proteolytically destroyed (28,30). Both MIR1 and MIR2 reduce the cell surface levels of MHC class I; MIR2 also selectively targets the costimulatory molecules B7.2 and ICAM-1, both of which are involved in the enhancement of helper T cell signaling (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27]. Like other herpesvirus family members, it encodes proteins that block MHC class I expression on the cell surface (28)(29)(30)(31). These are known as modulator of immune recognition (MIR) proteins; MIR1 and MIR2 are expressed during lytic replication and are encoded by the open reading frames K3 and K5, respectively.…”
Section: Introductionmentioning
confidence: 99%